2013
DOI: 10.1007/s11581-013-0926-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis, Raman spectroscopy and complex impedance analysis of Cu2+-doped KDP

Abstract: Raman spectroscopy and differential thermal analysis (DTA) and thermogravimetric analysis have been carried out on Cu-doped KH 2 PO 4 (Cu-KDP). X-ray diffraction powder data reveal that the structure of the KDP crystal does not change with the additive Cu 2+ ion. DTA analysis and Raman study of Cu-KDP as a function of temperature reveal that this compound undergoes two phase transitions at about Ttr =453 and 473 K. The electrical conductivity measurements on polycrystalline pellet of Cu-KDP (5) are performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Spectra at higher temperatures in the monoclinic phase similar to our spectra have been obtained before [24,25,28,29,33,34], including a peak at 1175 cm -1 . The broad peaks at about 1830, 2390 and 2710 cm -1 have also been seen [20,33,34] and were related to the intermolecular hydrogen bond network. Signs of dehydration composition were seen at high temperatures and pressures [28,29], and it may be that there exists another solid phase before the melting.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Spectra at higher temperatures in the monoclinic phase similar to our spectra have been obtained before [24,25,28,29,33,34], including a peak at 1175 cm -1 . The broad peaks at about 1830, 2390 and 2710 cm -1 have also been seen [20,33,34] and were related to the intermolecular hydrogen bond network. Signs of dehydration composition were seen at high temperatures and pressures [28,29], and it may be that there exists another solid phase before the melting.…”
Section: Resultssupporting
confidence: 84%
“…The room temperature Raman bands of KH 2 PO 4 have been assigned carefully, based on orientated single crystal studies at room temperature [21,[26][27][30][31] and calculations have been also done [36]. Spectra at higher temperatures in the monoclinic phase similar to our spectra have been obtained before [24,25,28,29,33,34], including a peak at 1175 cm -1 . The broad peaks at about 1830, 2390 and 2710 cm -1 have also been seen [20,33,34] and were related to the intermolecular hydrogen bond network.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…According to Som et al, the peak observed at 114 cm −1 may be assigned to K-PO 4 translatory vibrations [22]. The peak at 181 cm −1 can be assigned to the H 2 PO 4 rotational band [21]. The strongest peak at 914 cm −1 can be assigned to PO 4 totally symmetric stretching mode [23].…”
Section: Raman Spectroscopymentioning
confidence: 96%
“…Strukov et al 3 have made hysteresis loop and specific heat studies on KDP and DKDP crystals. Ettomi et al 4 have made thermal analysis studies on KDP and DKDP crystals. Chai et al 5 have made Raman scattering studies on KDP and DKDP crystals.…”
Section: Introductionmentioning
confidence: 99%